Using tuned mass damper inerter to mitigate vortex-induced vibration of long-span bridges: Analytical study. (1st March 2019) - Xu, Kun; Bi, Kaiming; Han, Qiang; Li, Xiaopeng; Du, Xiuli
Highlights: Adopted a novel TMDI system to control the undesirable VIV of long-span bridges. Proposed an optimization method for the TMDI-VIV system. Validated the efficiency of TMDI prior to TMD in VIV control of long-span bridges. Abstract: The undesirable vortex-induced vibration (VIV) may seriously influence the fatigue life and serviceability of bridge structures. It is important to take countermeasures to suppress the adverse VIV of long-span bridges. In the present study, a novel inerter-based system, namely the tuned mass damper inerter (TMDI), is proposed to control the VIV of the main deck of long-span bridges. In this system, an inerter device, which is able to transform the linear motion into the high-speed rotational motion and thus significantly amplifies the physical mass of the system, is incorporated into the conventional tuned mass damper (TMD) system to further improve the performance of TMD. An applicable layout of the TMDI inside the bridge deck is introduced and the governing equations of the structure-TMDI system subjected to VIV are established. The optimization of the TMDI parameters with the consideration of nonlinear aeroelastic effect is derived. The control performance and robustness of the proposed system are investigated through an analytical case study in both the time and frequency domains. It is observed that the TMDI system can obviously reduce the VIV responses of the bridge deck. Moreover, compared to the conventional TMD system, the static stretching of the spring due to gravity and the oscillation amplitude of the mass block in the TMDI system are significantly reduced. These properties make the proposed TMDI system an attractive alternative for the VIV control of long-span bridges.